Internet of Things Development for Flood Early Warning Monitoring System: A Review - Iqbal Fariansyah Ridwan (Journal of Computation Physics and Earth Science (JoCPES), 2023)
The purpose of this study is to conduct a systematic literature review. The process of writing a systematic literature review (SLR) is carried out in accordance with this framework. High rainfall during the rainy season can cause continuous rainfall and increase the volume of water that has the potential to cause flooding. Meanwhile, the community does not receive information or notification directly when this happens. To anticipate these problems, it is effective to develop a water level monitoring system as an IoT-based flood early warning tool. This paper is sourced from various publications on IoT-based flood detection systems. This study discusses the definition and selection of methods used in this study, what is the purpose of this study in developing an IoT-based flood detection system, how the results of the flood detection system that has been implemented are compared. In this paper, we present the results of the development of flood detection systems in each previous study. Therefore, the main purpose of this paper is to review research on the development of IoT-based flood detection systems.